RISKS AND PROSPECTS OF KAZAKHSTAN’S PARTICIPATION IN INTEGRATIVE INTERACTIONS WITHIN THE EAEU - DOSSYMKHAN, Yenglik; DYUSSEMBEKOVA, Maira; MUKASHEVA, Manshuk; KOZHAHMETOVA, Aigul (CENTRAL ASIA AND THE CAUCASUS, 2019)
The Eurasian Economic Union (EAEU) is currently one of the most important integrative structures in the post-Soviet territory. The expansion of the organization, military and political conflicts in the post-Soviet territory, world crises, and other factors directly influence the integrative union’s member countries and cause numerous questions regarding the future of the EAEU. Kazakhstan is one of the most important members of the Union, and the aforementioned processes also have a direct impact on it. The prospect of integrating new states, as well as an expansion of the Union’s powers and role and its transition to a political level, bring new challenges that require reconsideration and the establishment of new national policies in regard to both member countries and the EAEU as a whole. The current study analyzes the relevance and the peculiarities of the existence of a structure such as the EAEU in contemporary geopolitical realities, its influence on member countries (Kazakhstan in particular), and evaluates the risks and prospects for Kazakhstan as a member country.